Family appraisal of paediatric acquired brain injury: a social work clinical intervention trial. (3rd October 2018) - Hickey, Lyndal; Anderson, Vicki; Hearps, Stephen; Jordan, Brigid
ABSTRACT: Objective : To compare the efficacy of a new intervention ' Family Forward' with 'Usual Care' social work practice in optimising family appraisal of a child's acquired brain injury to ensure better adaptation during the inpatient rehabilitation phase of care and early transition home. Research Design : Single site, prospective, sequential comparison group design. Methods and Procedures : Families were recruited on admission to an inpatient rehabilitation service based at a tertiary paediatric hospital. The ' Usual Care' group ( n  = 22; 29 parents) recruitment, intervention and data collection were completed first (Phase 1), followed by the ' Family Forward' group ( n  = 25; 43 parents) (Phase 2). Parents/caregivers completed measures: (Impact of Event Scale- Revised: IES-R; Parents Experience of Childhood Illness and Brief Illness Perception Questionnaire: Brief IPQ) at the time of their child's inpatient rehabilitation admission, inpatient rehabilitation discharge, and 6 weeks post-discharge. Main Outcomes and Results : There were more children with traumatic brain injuries in the Family Forward group ( n  = 13) than Usual Care ( n  = 6) and the Family Forward group had a longer hospital admission (days, M  = 56.4, SD  = 46.1 vs. M  = 37.5, SD  = 16.4, p =  0.019). No significant group differences were found for family appraisal outcomes at any of the three time-points. Both groups reported reductions in trauma and grief responses, emotional experiences and perceptions of their child's injury at post-intervention and follow-up. Both groups continued to have depleted emotional resources (PECI scale) at 6 weeks post-discharge. Conclusions : The study contributes important insights into family appraisal experience in the early stages following paediatric acquired brain injury. In this context, 'Family Forward' needs to incorporate interventions that support and promote ongoing family appraisal as issues related to their child's injury arise over time. Future research is needed to focus on whether the Family Forward approach does sustain family system adaptation (a key aim informing the design of the intervention) over the longer term.